Strong-correlation induced high-mobility electrons in Dirac semimetal of perovskite oxide - Fujioka, J.; Yamada, R.; Kawamura, M.; Sakai, S.; Hirayama, M.; Arita, R.; Okawa, T.; Hashizume, D.; Hoshino, M.; Tokura, Y. (Nature communications, 2019)
Electrons in conventional metals become less mobile under the influence of electron correlation. Contrary to this empirical knowledge, we report here that electrons with the highest mobility ever found in known bulk oxide semiconductors emerge in the strong-correlation regime of the Dirac semimetal of perovskite CaIrO 3 . The transport measurements reveal that the high mobility exceeding 60,000 cm 2 V −1 s −1 originates from the proximity of the Fermi energy to the Dirac node (ΔE < 10 meV). The calculation based on the density functional theory and the dynamical mean field theory reveals that the energy difference becomes smaller as the system approaches the Mott transition, highlighting a crucial role of correlation effects cooperating with the spin-orbit coupling. The correlation-induced self-tuning of Dirac node enables the quantum limit at a modest magnetic field with a giant magnetoresistance, thus providing an ideal platform to study the novel phenomena of correlated Dirac electron. Electron correlation normally makes electrons less mobile, but it is still not clear when correlation becomes very strong in Dirac semimetals. Here, Fujioka et al. report a very high electron mobility exceeding 60,000 cm 2 V −1 s −1 in correlated Dirac semimetal of perovskite CaIrO3, due to the enhanced electron correlation nearby the Mott transition.